One bis-indole alkaloid-voacamine from Voacanga africana Stapf: biological activity evaluation of PTP1B in vitro utilizing enzymology method based on SPRi expriment - Yan-Qiu Wang; Hong-Xiang Li; Xiao-Chun Liu; Jin-Shuang Zhao; Rong-Qiang Liu; Wen-ying Huai; Wei-Jun Ding; Tian-E Zhang; Yun Deng (Natural Product Research, 2019)

Distinctiveness, speciation and demographic history of the rare endemic conifer Juniperus erectopatens in the eastern Qinghai-Tibet Plateau - Jingjing Xu; Xinya Song; Markus Ruhsam; Tingxuan Liu; Jialiang Li; Linda E. Neaves; Jibin Miao; Siyu Xie; Qingyu Meng; Kangshan Mao (Conservation Genetics, 2019)

The effect of substrate grain size on burrowing ability and distribution characteristics of Perinereis aibuhitensis - Tao Sun; Chun’e Liu; Xingzuo Li; Dongzhengyang An; Hairui Yu; Zheng Ma; Feng Liu (Acta Oceanologica Sinica, 2019)

Supporting Spartina : Interdisciplinary perspective shows Spartina as a distinct solid genus - Alejandro Bortolus; Paul Adam; Janine B. Adams; Malika L. Ainouche; Debra Ayres; Mark D. Bertness; Tjeerd J. Bouma; John F. Bruno; Isabel Caçador; James T. Carlton; Jesus M. Castillo; Cesar S. B. Costa; et al. (Ecology, 2019)
In 2014, a DNA‐based phylogenetic study confirming the paraphyly of the grass subtribe Sporobolinae proposed the creation of a large monophyletic genus Sporobolus , including (among others) species previously included in the genera Spartina , Calamovilfa , and Sporobolus. Spartina species have contributed substantially (and continue contributing) to our knowledge in multiple disciplines, including ecology, evolutionary biology, molecular biology, biogeography, experimental ecology, biological invasions, environmental management, restoration ecology, history, economics, and sociology. There is no rationale so compelling to subsume the name Spartina as a subgenus that could rival the striking, global iconic history and use of the name Spartina for over 200 yr. We do not agree with the subjective arguments underlying the proposal to change Spartina to Sporobolus . We understand the importance of both the objective phylogenetic insights and of the subjective formalized nomenclature and hope that by opening this debate we will encourage positive feedback that will strengthen taxonomic decisions with an interdisciplinary perspective. We consider that the strongly distinct, monophyletic clade Spartina should simply and efficiently be treated as the genus Spartina .

Intravitreal Ets1 siRNA alleviates choroidal neovascularization in a mouse model of age-related macular degeneration - Manhui Zhu; Li Jiang; You Yuan; Lili Chen; Xiaojuan Liu; Juan Liang; Qiujian Zhu; Dongmei Ding; E. Song (Cell and Tissue Research, 2019)

Copy number variation of bovine SHH gene is associated with body conformation traits in Chinese beef cattle - Mei Liu; Bo Li; Tao Shi; Yongzhen Huang; George E. Liu; Xianyong Lan; Chuzhao Lei; Hong Chen (Journal of Applied Genetics, 2019)

Computational detection and experimental validation of segmental duplications and associated copy number variations in water buffalo ( Bubalus bubalis ) - Shuli Liu; Xiaolong Kang; Claudia R. Catacchio; Mei Liu; Lingzhao Fang; Steven G. Schroeder; Wenli Li; Benjamin D. Rosen; Daniela Iamartino; Leopoldo Iannuzzi; Tad S. Sonstegard; Curtis P. Van Tassell; et al. (Functional & Integrative Genomics, 2019)

Changes in retinal and choroidal morphology after cerebrospinal fluid pressure reduction: a Beijing iCOP study - Lu Liu; Xiaoxia Li; Hanspeter E. Killer; Kai Cao; Jing Li; Ningli Wang (Science China Life Sciences, 2019)

Leveraging linkage evidence to identify low-frequency and rare variants on 16p13 associated with blood pressure using TOPMed whole genome sequencing data - Karen Y. He; Xiaoyin Li; Tanika N. Kelly; Jingjing Liang; Brian E. Cade; Themistocles L. Assimes; Lewis C. Becker; Amber L. Beitelshees; Adam P. Bress; Yen-Pei Christy Chang; Yii-Der Ida Chen; Paul S. de Vries; et al. (Human Genetics, 2019)

Adsorption performance and mechanisms of Pb(II), Cd(II), and Mn(II) removal by a β-cyclodextrin derivative - Mengjiao Zhang; Liyun Zhu; Changhua He; Xiaojun Xu; Zhengyang Duan; Shuli Liu; Mingyao Song; Shumin Song; Jiemei Shi; Yu’e Li; Guangzhu Cao (Environmental Science and Pollution Research, 2019)